Subsidies to the Rescue. The funding of poor relief in Flemish village communities during the crisis of the 1840s, a comparative analysis - Beeckaert, Esther (TSEG - The Low Countries Journal of Social and Economic History, 2019)
This article questions changes in the funding of local poor relief during the 1845- 1848 food crisis in Flemish village communities. This will be studied comparatively between three distinct regions in Flanders: inner-Flanders, coastal Flanders, and the Waasland. In all three regions it was local relief institutions that increased their financial capacity in order to accommodate rising poverty, despite the long-term advance of nationalized welfare in the background. However, considerable regional differentiation could be detected in the nature and degree by which the funding strategies were adapted. This is explained by three interrelated factors: the direct impact of the food crisis, structural economic developments and the political organization of poor relief.